EMPLOYEE TRAINING AND PERFORMANCE OF CIVILIANS IN BRITISH ARMY TRAINING UNIT CENTERS IN KENYA - Njeri, Wangari Alice; Waithaka, Dr. Paul (European Journal of Business and Strategic Management, 2019)
Purpose: BATUK is an organization that trains UK army personnel on light force operations here in Kenya. BATUK employs civilians workforce component to offer support services to the training troops. The main objective of this study was to find out the effect of training on the performance of employees at BATUK. Methodology: The study utilized a descriptive survey research design and the target population comprised of all the 520 permanent staff members of BATUK. The sample of this study was 156 BATUK employees. This was selected through stratified random sampling technique. The study used primary data which was largely quantitative and descriptive in nature. The study used a semi-structured questionnaire. The questionnaires were self-administered with the help of two research assistants using a drop and pick method. After quantitative data was obtained through questionnaires, it was prepared in readiness for analysis by editing, coding, categorizing and keyed into statistical package for social sciences (SPSS) computer software for analysis. Descriptive and inferential statistics such as sampling were used to analyse the data. Microsoft excel was used to complement SPSS in data analysis. The particular descriptive statistics included frequencies and means while the particular inferential statistics, correlation analysis and regression. Results: The research findings indicate that types of training have positive correlation to employee's performance. On the job training had the highest occurrence as a type of training amongst other types of training. Unique Contribution to Theory, Practice and Policy: The research recommends that training should be encouraged. More funding should be directed to on the job training as it showed to be the most effective. Online training, Team work training and instructor led training should be expounded to compliment on the job training.